دور الآخر في تشكيل الحوار الحضاري من خلال رواية السموم لعلي عبيد - زواري فرحات, عمارة (جامعة الوادي - University of Eloued, 2023)
جاءت مقولة الحوار بين الحضارات، كرد فعل على مصطلح "الصراع بين الحضارات"، فقد جاد كثير من الكتاب العرب-ومن بينهم علي عبيد- على التجديد في صياغة الآخر المثالي الذي عكس النظرة المتوارثة التي خلفها الصراع الحضاري حول هذا الآخر، على أنه نقيض أو عدو، وهذا ما سعت إليه رواية السموم لطرحه وقامت بكشف الستار لمرحلة جديدة، قائمة على أحقية امتلاك هوية الذات وزعزعة كل مركزية ثقافية كانت أم حضارية. The saying of dialogue among civilizations was a reaction to the term "conflicts among civilizations", Many Arab writers - Ali Abid among them - renew the formulation of the perfect other that reflected the outlook or the legacy of the civilizational conflict over this other, as a contradiction or enemy, the Novel "simoon" seeks to roll out and unveiled a new phase based on eligibility the one's own identity and to destabilize every cultural and civilized centrality.
Keywords: الأنا والأخر ; الحوار الحضاري ; صورة الأخر ; رواية السموم